The struggle and Islamic patriotism of Sunan Kalijaga in folktales of Central Java, Indonesia - Wardani, Nugraheni E. (HTS teologiese studies, 2023)
This study aims to describe and explain (1) the hero figure and his worldview in the folktales ‘The Legend of Sunan Kalijaga’ and ‘The Legend of Ki Ageng Pandanaran’; and (2) Sunan Kalijaga’s struggle and patriotism in the two folktales. This research is an exploratory qualitative research. The data of this research were two folktales of Central Java and informants. Data collection techniques by analysing two folktales and notes on the results of interviews with informants. Data analysis was then employed in the interactive model. The results revealed that the hero figure in the two folktales was Sunan Kalijaga. Sunan Kalijaga faced deteriorating social conditions, that is, the condition of poor people and rulers who acted arbitrarily towards the people by collecting high tributes, who were extravagant, and who only focused on personal wealth and power. In the face of deteriorating social conditions, Sunan Kalijaga had a world view of Islamic religious humanism. Islamic religious humanism means humanising humans according to their role as abdullah and khalifah on earth. In addition, the Islamic struggle and patriotism of Sunan Kalijaga were shown in efforts to spread Islam as a rahmatan lil alamin [religion that aims to give universal love to fellow human beings and the universe and is opposed to violence against fellow humans and the universe] by emphasising tasawuf, makrifat and dakwah.Contribution: This study contributes to conveying the development of Islamic teachings in Indonesia, which were disseminated by Sunan Kalijaga as rahmatan lil alamin, not Islam that developed through methods and teachings of violence.